Eleocharis carniolica W. D. J. Koch, new species in flora of Montenegro - Vuksanović, Nada; Bubanja, Nada; Berg, Christian (Hacquetia, 2019)
During floristic research of acidic bogs, calcareous fens and seasonally flooded (periodically inundated) grassy places in beech forests in Semolj region, Eleocharis carniolica W. D. J. Koch was found, which was the first record of that species in vascular plant flora of Montenegro. In surrounding countries, this species was recorded in Bosnia and Herzegovina, Croatia, Slovenia and Albania. This paper provides description of sites, habitat and ecology of Eleocharis carniolica W. D. J. Koch in Montenegro.